Health Provider’s Characteristics Associated With Side Effects Of Contraceptive Use In Indonesia - Syahrida Wahyu Utami,; Lestari, Nur Cahyani Ari; Barkinah, Tut; Wahyuni, Rahmawati; Deananda, Deananda (Jurnal Ners, 2025)
Contraceptive use is important in birth control and family planning, with various methods tailored to individual needs and health conditions. This study aims to explore more deeply the characteristics of service providers and the side effects of contraception used in Indonesia. This study used secondary data from the Indonesian Family Survey (IFLS) to analyze contraceptive side effects in 8,167 women selected through stratified random sampling. The main focus was the type of health service provider, with analysis using univariate, bivariate, and multivariate techniques through binary logistic regression. Nearly 40% of women experience contraceptive side effects, influenced by age, provider type, and contraceptive method. Women who receive services from community health centers or private clinics tend to experience fewer side effects than those who receive services from hospitals. Use of the pill or permanent methods is also associated with fewer side effects. Therefore, education and training for health care providers need to be improved to ensure appropriate counseling.